Representation of Female Subjugation in W.B. Yeats’ Leda and The Swan (Pursuits: A Journal of English Studies, 2025)
This paper examines the representation of female personality in W.B. Yeats’ Leda and the Swan. The current study shows that the female figure in the poem is subjugated because of male domination in terms of sexuality. The poem reflects the sex hierarchy of the contemporary time. Leda represents women forced to participate in sexual activity in patriarchy. She is objectified and swan as a metaphor of a hedonist man satisfies his lust. The major finding is that sexual objectification forces women to internalize that they are just for the use by men. Therefore, they remain passive as portrayed in the poem. The research has used the textual analysis as the research method and the rhetorical devices used in the poem are analyzed to explore the depiction of female status as predominant in the contemporary society of the United Kingdom. Leda is presented as a passive object to be brutally raped and desired. She is at the center of numerous conflicts. She directly struggles with Zeus. However, the poet has used Leda as a means for an understanding of the possibilities for transformation. Patriarchy serves as a cross-generational burden for the glorification of women as depicted in the poem. There has been a change in the sense that women had been treated equally and in a dignified manner in the ancient time. However, their status changed in the early modern era as implied in the poem.